Enhancing critical thinking with realistic mathematics education: Insight from learning styles, thinking habits, and cognitive abilities - Allen Marga Retta; Ratu Ilma Indra Putri; Zulkardi; Ely Susanti (Jurnal Elemen)
Although critical thinking is vital in 21st-century learning, mathematics classes often emphasise procedures over reasoning. Few studies have explored how students’ characteristics (learning styles, thinking habits, and cognitive abilities) interact with contextual learning approaches such as Pendidikan Matematika Realistik Indonesia (PMRI). This study aimed to describe the students’ critical thinking using PMRI as a learning approach, specifically by analysing how these abilities vary based on students’ learning styles, thinking habits, and cognitive ability levels. The context of water pH was used to explore the measures of central tendency. Students were observed based on their learning styles, thinking habits, and cognitive abilities. This study used a descriptive qualitative method with 29 eighth-grade students from junior high school in Palembang. Data were collected through tests, questionnaires (learning styles and thinking habits), and the participants’ academic records. The data were analysed using Miles, Huberman, and Saldana’s model, which involves data reduction, presentation, and conclusions. The results show that female students tend to possess “quite critical category”, while male students also show “quite critical category” category when analysed by learning style, but lower in thinking habits and cognitive ability. This implies that teaching should consider students' differences to support the development of critical thinking.